Planeamiento estratégico para incrementar el nivel de presencia de "Comercial Chancafe" en el distrito de Huamachuco. - Saavedra Cuevas, Egon (2012)
Currently companies have to accept new challenges and to learn to cope with competition, if they have a loyal commitment to their future. So, should set aside empiricism and start using tools and techniques to support, they effectively leading to better results. This study uses the Strategic Planning as a key tool to drive “COMERCIAL CHANCAFE” Chain Stores, to increase the level of competence of the company. The Strategic planning applied to this study, comprising: an internal diagnosis (using the evaluation matrix of internal factors and the value chain) as well as an external diagnosis (using the evaluation matrix of external factors, the Porter diamond diamond and competitive profile matrix). Then with the SWOT matrix identified the strengths, weaknesses, opportunities and threats of the company. In the creative phase was determined or philosophical vision, mission and company values. Then move on to the strategic phase, which identified strategies to be followed by the company to achieve its objectives. Later in the implementation phase projects were determined to continue to achieve the strategies. Culminating with the control phase to set standards to be maintained by the company for insurance that will eventually reach and meet the objectives, conclusions and recommendations proposed.